2020
DOI: 10.1109/access.2020.3009387
|View full text |Cite
|
Sign up to set email alerts
|

Coal Mine Rescue Robots Based on Binocular Vision: A Review of the State of the Art

Abstract: Rescue work after a coal mine accident is fraught with challenges and dangers. Considering the safety of rescue workers and the urgency of a rescue mission, it is necessary to use coal mine rescue robots to perform the tasks of environmental detection and rescue. As a key part of the robot sensing system, a visual sensor can provide much information about a scene. Among vision sensor types, binocular vision has the advantages of being noncontact and passive, and it is the key technology for a robot to acquire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…H, W represents the height and width of image. The mask can be calculated as (10). N denotes the number of 1.…”
Section: B Evaluation Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…H, W represents the height and width of image. The mask can be calculated as (10). N denotes the number of 1.…”
Section: B Evaluation Metricsmentioning
confidence: 99%
“…If the precisely disparity can be estimated, we can get the exactly depth. Therefore, stereo disparity estimation from a pair of stereo images has drawn more and more attention, which is also widely used in 3D reconstruction [2], [3], augmented reality (AR) [4], [5], self-driving [6], [7] and robotics [8]- [10]. The traditional stereo disparity estimation methods can be divided into global energy function [11], [12] and local similarity [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have developed a variety of depth detection sensors to obtain depth data, such as infrared distance sensor [ 2 ], ultrasonic distance sensor [ 3 ], laser distance sensor [ 4 ]. In recent years, higher-performance depth detectors, such as binocular cameras [ 5 , 6 , 7 , 8 , 9 ], millimeter-wave radar [ 10 , 11 ] and lidar [ 12 , 13 , 14 , 15 , 16 ] have also been equipped on UAVs to complete relevant missions. Researchers also found that the accuracy of depth information can be effectively improved by using several depth detectors simultaneously [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The feature extraction can be realized by the visual measurement system after image acquisition and processing of the object. According to the dimension information, visual measurement can also be divided into monocular measurement [8,9] and multi-ocular measurement [10]. Monocular measurement is simple in structure, light in weight and low in cost, but it is difficult to obtain the depth information of objects.…”
Section: Introductionmentioning
confidence: 99%